Zakaz łączenia funkcji z członkostwem w zarządzie spółki kapitałowej – zagadnienia wybrane - Mizerski, Dominik (Wydawnictwo Naukowe UAM, 2021)
W artykule przedstawiono najważniejsze instytucje prawne ograniczające lub wyłączające pełnienie przez członków zarządu określonych funkcji. Opisano m.in. zakaz łączenia stanowisk członka zarządu z członkostwem w radzie nadzorczej tej spółki oraz poruszono problematykę dopuszczalności ustanawiania członków zarządu spółki jej pełnomocnikiem czy prokurentem. W opracowaniu poruszono także problematykę sankcji za złamanie nałożonych na członków zarządu zakazów oraz ograniczeń w pełnieniu innych funkcji ze wskazaniem rozbieżności w doktrynie oraz orzecznictwie w zakresie konsekwencji naruszenia powyższych ograniczeń.

The article presents main legal institutions restricting or excluding the performance of certain functions by the members of management boards. The article describes, among others, the prohibition of combining the position of a management board member with the membership in the supervisory board of the same company and elaborates on the issue of admissibility of appointing members of the company's management board as its proxies or commercial proxies. The paper also focuses on the issue of sanctions for a breach of prohibitions and restrictions imposed on the members of a management board in performance of other functions, indicating the differences of the doctrine and jurisprudence views on the consequences of the breach of the abovementioned limitations.
Prohibition on combining functions with the membership of the management board of a company – selected issues
Keywords: członkostwo w zarządzie; niepołączalność funkcji; reprezentacja spółek; zakaz konkurencji; membership of the management board; incompatibility of functions; representation of companies; non-competition